Upaya Kepolisian Dalam Penegakan Hukum Terhadap Pelaku Tindak Pidana Tabrak Lari Di Kota Gorontalo - Karim, Abdul Rahman; Ismail, Dian Ekawaty; Imran, Suwitno Y. (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
The increasing number of motorized vehicles every year which is not matched by road facilities and human negligence often results in traffic accidents. A traffic accident where the perpetrator is irresponsible, by leaving the victim alone without stopping the vehicle, and not providing assistance is called a hit and run. The crime of hit and run is a problem that needs to be addressed because it is an immoral act and harms other people. This study aims to find out and analyze what are the factors that cause a lot of hit-and-runs in Gorontalo City and the efforts of the police in enforcing the law against the perpetrators of hit-and-run crimes in Gorontalo City. The type of research used is empirical juridical. This research is descriptive in nature. The location of this research is the police who have the authority to enforce the law against hit-and-run crimes, namely the Gorontalo City Police Traffic Unit Accident Unit. There are 2 factors causing hit-and-run crimes in the City Region of Gorontalo City, namely individual / personal factors caused by the negligence of the vehicle driver accompanied by a lack of legal awareness of the person himself. Furthermore, situational factors/conditions due to quiet road conditions, not many witnesses, so that it is possible for the perpetrators to escape from their responsibilities and forced circumstances which can threaten the safety of the perpetrators from the tantrums of the masses and the condition of the driver who is powerless to provide assistance.